In vitro Antimicrobial Activity, Lipid Content and Physico-Chemical Analysis of Non-Edible Oils - B. Bhagat, Rani; Kulkarni, D.K. (Asian Journal of Chemistry, 2010)
Antimicrobial activity of 7 non-edible seed oils on 7 species of microbial organisms were examined against Bacillus cereus, Staphylococcus aureus, Escherichia coli, Shigella sonnei, Klebsiella pneumoniae, Streptococcus fecalis and Shigella dysentrae. These are examined using agar well diffusion method against 7 bacteria. The seed material of non-edible oil resources were extracted using pet ether by soxhlet apparatus. The extracts were studied for fatty acid profile by gas chromatography and showed presence of palmitic acid, stearic acid, oleic acid, linoleic acid and linolenic acid. Physico-chemical properties like, oil colour, oil content (%), moisture (%), ash (%), specific gravity, refractive index, acid value, iodine value, free fatty acid, saponification value, mean molecular mass, content of nitrogen (%) and protein (%) were carried out. This paper reports on preliminary screening of the in vitro antimicrobial activities against 7 human pathogenic bacteria, lipid content and physicochemical analysis of non edible oil yielding plant species.